Domestic water demand predicting by factors analysis of planned colony in Ajmer, Rajasthan (India) - Singh, Ganpat; Goel, Arun; Choudhary, Mahender (International Journal of Computer Sciences and Engineering, 2025)
In this paper, contribution of variables of domestic urban water demand considered for the purpose of prediction of urban water supply in planned colonies of the City of Ajmer. The data for these 15 variables are entered in the factor analysis under principal component, generalised least square and maximum likelihood method, and five factors/variables are extracted, comprising combinations of these 15 variables. Based on these five principal components (PCs) variables a multi linear regression (PCR) coefficient of 0.76, 0.64 and 0.62 are obtained by the principal component, generalised least square and maximum likelihood model respectively. These five significant principal components are further fed into a multilayer perceptron neural network (NN) model for water demand forecasting. The linear regression coefficient of MLP NN (PCs) is 0.76, very close to the principal component multiple linear regression (stepwise) coefficient of 0.76, and verifying the dependence of water demand on these five principal components. The better result is showing by factor analysis under PCR compare to the factor analysis under Maximum Likelihood and Generalised Least Square methods. The lowest average percentage difference of predicted value is -2.64 PCs MLP (NN) and -2.08 were giving by PCR (PC) respectively. The outcome of the study suggests that the extracted variables are significant for estimation of water demand for planned colonies of Ajmer city.